Fat accumulation in the liver of obese rats is alleviated by soy protein isolate through β‐catenin signaling. (13th June 2013) - Zhou, Dan; Lezmi, Stephane; Wang, Huan; Davis, Jeremy; Banz, William; Chen, Hong
<x xml:space="preserve">Abstract</x> Objectives To investigate the effects of soy protein isolate (SPI) on Wnt/β‐catenin signaling in the liver of obese rats, as well as the roles of this pathway in regulating the hepatic fat accumulation. Design and Methods Obese and lean Zucker rats were fed diets containing either casein or SPI as protein source for 17 weeks. Histology and biochemical analysis, real‐time PCR, Western blot, immunostaining, short interfering RNA assay were performed for liver samples. Results Our study showed that fat content was significantly lowered in the liver of SPI‐fed obese rats, accompanied by a reduction in hepatocellular vacuolation, compared to the casein‐fed control. β‐Catenin protein level in the liver of obese rats was downregulated compared to the lean group, indicating that the obese genotype exhibits an overall reduction in Wnt signaling. Importantly the repression of β‐catenin in the obese rats was alleviated by feeding the SPI diet. siRNA treatment in rat hepatoma cells confirmed that silencing of β‐catenin exacerbated fatty acid‐induced fat accumulation, which implicated an important function of Wnt/β‐catenin signaling in hepatic fat metabolism. Conclusion SPI intake restored β‐catenin signaling and alleviated hepatic fat accumulation and liver damage in the obese rats.